Risk Factors Associated with Scabies Occurring in Islamic Boarding Schools: Literature Review - Aziz Setiawan; Qomaruddin, Mochammad Bagus; Sulistyowati, Muji (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Islamic boarding schools in Indonesia, in particular, have classic health problems. Some diseases that are common in Islamic boarding schools are scabies, shortness of breath, fever, fainting, cough and cold with influenza, gastritis/ulcer, and so on. And the most common health problem in Islamic boarding schools is scabies. It seems that students who live in boarding schools are "obliged" to experience an itchy disease characterized by symptoms of mruntus (pustules), redness, and itching. There is a saying that being a boarding school student is not valid if you don't suffer from itchy skin. Scabies and hut children's diseases are the same. Personal health, knowledge, teacher and peer support are some of the causes. Aims: The purpose of this literature review was to identify some risk factors for scabies in Indonesian Islamic boarding schools. Method: The research was conducted using relevant literature databases, such as google scholar,n SageJournal and PubMed. The keyword used for this literature review was "scabies in Islamic boarding schools". The literature search was limited from 2013 - 2022. There were 11 articles that were relevant and related to scabies that occurred in boarding schools. Results: The results of the 11 articles showed that personal hygiene has a lot to do with and even influences the incidence of scabies in some boarding schools. Conclusion: So improving the personal hygiene of students is one of the important factors in preventing the incidence of scabies in Islamic boarding schools.